2005
DOI: 10.1352/0047-6765(2005)43<1:bwsaaw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Status Among Adults With Intellectual Disability in the Community

Abstract: The prevalence of obese, overweight, and healthy weight adults with intellectual disability in the community was estimated using data from the National Health Interview Survey from 1985 to 2000. Using the Body Mass Index (BMI) as a measure, the percentage of adults with intellectual disability in the obese category was higher than that for the general population and increased over the 16-year period. There was no similar detectable trend for adults with intellectual disability who were in the overweight catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
128
2
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 13 publications
9
128
2
8
Order By: Relevance
“…We reviewed the full texts of 148 articles once seven articles from other sources had been added (Figure 3). The authors of seven studies [91][92][93][94][95][96][97] were contacted for information regarding their studies; five authors replied and two studies 94,95 were deemed suitable to be included in the systematic review and meta-analysis. We also included a study 93 by one of the authors who did not reply, after we had reread and discussed the article collectively in more depth.…”
Section: Study Selectionmentioning
confidence: 99%
“…We reviewed the full texts of 148 articles once seven articles from other sources had been added (Figure 3). The authors of seven studies [91][92][93][94][95][96][97] were contacted for information regarding their studies; five authors replied and two studies 94,95 were deemed suitable to be included in the systematic review and meta-analysis. We also included a study 93 by one of the authors who did not reply, after we had reread and discussed the article collectively in more depth.…”
Section: Study Selectionmentioning
confidence: 99%
“…Several studies conducted in the United States have reported a higher prevalence of obesity among persons with ID compared to non-ID citizens [e.g., Rubin et al, 1998;Harris et al, 2003;Rimmer and Wang, 2005;Yamaki, 2005]. In particular, women, older individuals, and those with less severe disabilities and certain genetic causes of obesity (i.e., Down syndrome) were more likely to be obese compared to their counterparts [Fox and Rotatori, 1982;Kelly et al, 1986;Rimmer et al, 1993;Rubin et al, 1998].…”
Section: Obesity Prevalence In American Adults With Idmentioning
confidence: 99%
“…The researchers reported that the rate was significantly higher for the U.S. participants compared to participants from other countries. Yamaki [2005] estimated obesity prevalence among adults with ID by analyzing U.S. population-level household survey data. This data set was more likely to include a broader representation of people with ID who were supported by family members in the community but were not necessarily part of the ID service system [Fujiura, 1998;Yamaki and Fujiura, 2002].…”
Section: Obesity Prevalence In American Adults With Idmentioning
confidence: 99%
See 2 more Smart Citations